THE APPLICATION OF THE PRINCIPLE OF COHERENCE IN AL-HASHR: PERSPECTIVE OF QAWAID TAFSIR BY KHOLID BIN UTSMAN AL-SABT - Muhammad Faisal Purnomosidi; Andri Nirwana AN; Qoree Butlam (Universitas Muhammadiyah Surakarta, 2024)
Qawaid Tafsir by Khalid bin Uthman as Sabt is a book that formulates the sciences of exegesis into the form of rules, including reasonable calm in the Qur'an, he formulated three rules about reasonableness. First, most verses close with al-asma' al-husna to show that the message of the verse relates to these great names. Second, two adjacent verses or sentences, clearly or unclearly related, must have a unifying facet. Third, the general steps to find plausibility between verses in the Qur'an are to look for the surah, make provisional conclusions, analyze the provisional conclusions, and draw up the conclusion. This research is qualitative. Primary data sources are QS Al Hasyar, and secondary sources are the books